The electrical systems design & specification handbook for industrial facilities - Marrano, Steven J. (Fairmont Press ; Distributed by Prentice Hall PTR, 1998)
Written to serve the needs of today's competitive construction industry professionals, this practical handbook provides a consolidated guide for design engineers and project managers, as well as maintenance professionals, technicians, and others who must accurately specify electrical equipment. You'll find complete guidelines for short circuit calculations, load tabulation, equipment selection, and lighting design. Convenient specifier's checklists are provided for panelboards, medium voltage switchgear, motor control centers, induction motors, dry-type transformers, and transfer switches. A detailed discussion of circuit breakers and fuses in low voltage power systems is also included, along with coverage of design coordination, electrical scope development, drawing estimating sections, and a special chapter addressing data requirements for power systems studies.